A Method for Rapid Screening of Anilide-Containing AMPK Modulators Based on Computational Docking and Biological Validation - Mok, Simon W. F.; Zeng, Wu; Niu, Yuzhen; Coghi, Paolo; Wu, Yujun; Sin, Wai Man; Ng, Sio Ian; Gordillo-Martínez, Flora; Gao, Jia Yin; Law, Betty Y. K.; Liu, Liang; Yao, Xiaojun; et al. (Frontiers in Pharmacology, 2018)
Adenosine 5’-monophsphate-activated protein kinase (AMPK) is a crucial energy sensor for maintaining cellular homeostasis. Targeting AMPK may provide an alternative approach in treatment of various diseases like cancer, diabetes, and neurodegenerations. Accordingly, novel AMPK activators are frequently identified from natural products in recent years. However, most of such AMPK activators are interacting with AMPK in an indirect manner, which may cause off-target effects. Therefore, the search of novel direct AMPK modulators is inevitable and effective screening methods are needed. In this report, a rapid and straightforward method combining the use of in silico and in vitro techniques was established for selecting and categorizing huge amount of compounds from chemical library for targeting AMPK modulators. A new class of direct AMPK modulator have been discovered which are anilides or anilide-like compounds. In total 1,360,000 compounds were virtually screened and 17 compounds were selected after biological assays. Lipinski’s rule of five assessment suggested that, 13 out of the 17 compounds are demonstrating optimal bioavailability. Proton acceptors constituting the structure of these compounds and hydrogen bonds with AMPK in the binding site appeared to be the important factors determining the efficacy of these compounds.